2014
DOI: 10.1111/dar.12149
|View full text |Cite
|
Sign up to set email alerts
|

Regional abundance of on‐premise outlets and drinking patterns among Swiss young men: District level analyses and geographic adjustments

Abstract: Among Swiss young men, the density of outlets and, in particular, the abundance of bars, clubs and other on-premise outlets was associated with drinking level and HED, even when drinking consequences were not significantly affected. These findings support the idea that outlet density needs to be considered when developing and implementing regional-based prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…In contrast, density of off-premise alcohol outlets had no association with both current drinking and binge drinking. Previous studies have also found that on-and off-premise outlets are differently related to drinking behaviors (Astudillo et al, 2014;Connor et al, 2011;Kypri et al, 2008). The difference in drinking cultures and population characteristics may be the reason underlying the discrepancy across studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, density of off-premise alcohol outlets had no association with both current drinking and binge drinking. Previous studies have also found that on-and off-premise outlets are differently related to drinking behaviors (Astudillo et al, 2014;Connor et al, 2011;Kypri et al, 2008). The difference in drinking cultures and population characteristics may be the reason underlying the discrepancy across studies.…”
Section: Discussionmentioning
confidence: 91%
“…A third option is to restrict the number of alcohol outlets, especially the onpremise outlets. As stated before, evidence does suggest that reductions in availability of alcohol outlets can have significant impacts on drinking behavior and negative alcohol-related consequences (Astudillo et al, 2014;Huckle et al, 2008;Kuntsche et al, 2008;Kypri et al, 2008;Livingston et al, 2008). Other approaches could be to reduce the availability of social sources of alcohol, to put more control on the sale behavior, and to modify drinking norms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies using individual‐level data commonly analyse the number of outlets around, or the distance to the nearest outlet from participants' residences [54–57].…”
Section: Resultsmentioning
confidence: 99%
“…For an increase in price by 1 Swiss franc, for example, there was a decrease in the number of drinks by 10.8 % for people without AUD, 10.5 % for those with mild AUD, and 9.9 % for those with severe AUD. A multilevel analysis linked the individual level of drinking with the outlet density of communities (Astudillo, Kuendig, Centeno-Gil, Wicki, & Gmel, 2014). The density of on-premises outlets (bars or clubs where alcohol is sold for direct consumption), but not off-premise outlets (where alcohol is sold for consumption elsewhere), was associated with RSOD (having 6 drinks or more on a single occasion).…”
Section: Structural Measures Economic and Physical Availabilitymentioning
confidence: 99%